Business Process Management – The Perspective of Polish Banks and Insurance Companies - Agnieszka Bitkowska; Damian Dziembek; Tomasz Gzik (Communications of International Proceedings, 2022)
Today's economy is undergoing a dynamic process of change that is making the service sector, the so-called servitization, dominant (Kowalkowski et al., 2017, p. 4-10). In highly developed countries, 70% of gross national income comes from the service sector (Piątkowska (ed.), 2015, p. 203). In Poland, more than half of the companies (52.5%) are engaged in service activities (Skowrońska, Tarnawa (ed.), 2021, p. 6). The service sector is one of the most important and fastest-growing sectors of the Polish economy – both before and during the COVID-19 pandemic, and its role is likely to increase even further after the pandemic ends (Popławski et al., 2021, p. 6).